2010
DOI: 10.1021/jp104969c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Phase Transition, Surface Tension, and Nucleation Rate Predictions for Argon

Abstract: In this work, a weighted density functional theory has been used to study the equilibrium and metastable processes for argon. In the theoretical approach, the two- and three-body interactions of the fluid molecules are considered simultaneously, and the renormalization group transformation is applied to address the long-range fluctuations inside the critical region. The global phase equilibria, planar and curvature-dependent surface tensions, critical radius, and nucleation rates of argon are investigated syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Subsequent studies, however, have also found δ to be negligible or even equal to zero [20,63,76], positive and larger than σ [25,66], negative with −σ < δ < 0 [22,24,77] or negative and diverging (δ 0 = −∞) in the planar limit [78], while others have claimed that the sign of δ is curvature dependent itself [79,80]. Thereby, they have only proven the mutual inconsistency of their assumptions and methods, while nothing is truely known about δ and the dependence of the surface tension on curvature.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequent studies, however, have also found δ to be negligible or even equal to zero [20,63,76], positive and larger than σ [25,66], negative with −σ < δ < 0 [22,24,77] or negative and diverging (δ 0 = −∞) in the planar limit [78], while others have claimed that the sign of δ is curvature dependent itself [79,80]. Thereby, they have only proven the mutual inconsistency of their assumptions and methods, while nothing is truely known about δ and the dependence of the surface tension on curvature.…”
Section: Discussionmentioning
confidence: 96%
“…Approximate theoretical approaches suggest that the inclusion of three-body interactions will lead to more accurate predictions of the surface tension. 20,29 In this paper, we calculate the surface tension of argon by molecular simulation using the Monte Carlo method with a three-body potential. We show that an excellent agreement can be found with experimental data, providing that the longrange corrections are included with care and that a sufficiently large cut-off is used to avoid the need for the inclusion of the long-range correction to the potential energy at each step in the Markov Chain.…”
Section: Introductionmentioning
confidence: 99%
“…36,37,39 The size of the simulation box that we chose is 70 × 70 × 70 in lattice unit. Periodic boundaries conditions were employed in x-and y-directions, while a mirror boundary condition was used in z-direction.…”
Section: Model and Methodsmentioning
confidence: 99%